Gender- and age-related differences in osteoclast formation from circulating precursors. - Jevon, M; Sabokbar, A; Fujikawa, Y; Hirayama, T; Neale, S; Wass, J; Athanasou, N (2002)
A number of bone diseases characterised by excessive osteolysis (e.g. osteoporosis and Paget's disease) exhibit a marked gender difference in prevalence and are more common in the elderly population. Bone resorption is carried out by osteoclasts, which are formed by fusion of circulating mononuclear precursor cells of haematopoietic origin. In this study, we have determined whether there are gender- and age-related differences in osteoclast formation from circulating precursors. Peripheral blood mononuclear cells (PBMCs) were co-cultured with UMR106 osteoblast-like cells in the presence of macrophage-colony stimulating factor (M-CSF) and 1,25 dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) or cultured alone in the presence of sRANKL (soluble receptor activator of nuclear factor kappa B ligand) and M-CSF. As assessed by the formation of tartrate resistant acid phosphatase (TRAP)-positive (TRAP(+)) and vitronectin receptor-positive (VNR(+)) multinucleated cells (MNCs), there was no difference in the number of circulating osteoclast precursors in males and females. Lacunar resorption carried out by osteoclasts formed from these precursors was generally increased in males compared with females (P=0.03). An increase in the number of TRAP(+) and VNR(+) MNCs formed from male PBMCs was noted in response to 1,25(OH)(2)D(3) (P<0.005). An increase in lacunar resorption in cultures of PBMCs (10(5) per well) from males was also noted in response to 10(-9) M 1,25(OH)(2)D(3) (P<0.05) and sRANKL (P=0.05), but not M-CSF. The addition of dexamethasone resulted in a marked increase in osteoclast formation and lacunar resorption in both males and females. Post-menopausal females and males of comparable age showed similar levels of osteoclastogenesis. Pre-menopausal women showed similar levels of osteoclastogenesis but less resorption (P=0.01) compared with males of comparable age. These results show that there are specific gender/age-related differences in osteoclast formation and bone resorption and have implications for evaluating osteoclastogenesis in skeletal diseases such as primary osteoporosis and Paget's disease.